Force-velocity profiling in ice hockey skating: reliability and validity of a simple, low-cost fieldmethod - Stenroth, L.; Vartiainen, P.; Karjalainen, P. A. (Sports Biomechanics, 2023)
In recent years, a simple method for force-velocity (F-v) profiling, based on split times, has emerged as a potential tool to examine mechanical variables underlying running sprint performance in field conditions. In this study, the reliability and concurrent validity of F-v profiling based on split times were examined when used for ice hockey skating. It was also tested how a modification of the method, in which the start instant of the sprint is estimated based on optimisation (time shift method), affects the reliability and validity of the method. Both intra- and inter-rater reliability were markedly improved when using the time shift method (approximately 50% decrease in the standard error of measurement). Moreover, the results calculated using the time shift method highly correlated (r > 0.83 for all variables) with the results calculated from a continuously tracked movement of the athlete, which was considered here as the reference method. This study shows that a modification to the previously published simple method for F-v profiling improves intra- and inter-rater reliability of the method in ice hockey skating. The time shift method tested here can be used as a reliable tool to test a player`s physical performance characteristic underlying sprint performance in ice hockey skating.